Analisis Representasi Visual Siswa Dalam Pembelajaran Matematika Berbasis Etnomatematika Digital - Karlina Handayani; Ratu Sarah Fauziah Iskandar; Ahmad Fadillah (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study addresses the issue of students’ low ability in constructing meaningful mathematical visual representations, which are often limited to reproductive forms. To overcome this, ethnomathematics is utilized as an approach to relate mathematical concepts with local cultural contexts, making learning more contextual and meaningful. The purpose of this research is to explore how students construct mathematical visual representations through ethnomathematics-based learning supported by digital media. This study employs a descriptive qualitative approach involving tenth-grade students at MAN 2 Kota Tangerang selected purposively. Data were collected through classroom observations, documentation of students’ work, and interviews, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that ethnomathematics facilitates students in recognizing patterns and transforming cultural visuals into mathematical representations. However, students demonstrate varying levels of ability, ranging from reproductive, transitional, to conceptual stages. While ethnomathematics shows strong potential in improving students’ visual representation skills, appropriate scaffolding is still required to support deeper conceptual understanding. These results highlight the importance of integrating ethnomathematics into mathematics learning to foster more meaningful and contextual comprehension.Keyword: visual mathematical representation; digital ethnomathematics